PENGARUH GAYA KEPEMIMPINAN, PENYEMPURNAAN SISTEM ADMINISTRASI, SUMBER DAYA MANUSIA, REWARD DAN PUNISHMENT TERHADAP PENYUSUNAN ANGGARAN BERBASIS KINERJA (Study Empiris Pada SKPD Kabupaten Pelalawan) - Hotdianty, Hertika; Taufik, Taufeni; Haryani, Eka (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
The aim of this research is to analyze the effect ofthe leadership style, the perfection of administration, human resources, reward, and punishmenttoward performance based budgeting. The population of this research chief head of division, financial subsections, and financial staff that work on the unit of work in the SKPD Kabupaten Pelalawan.The sampling technique using purpose sampling. Total respondents in this research are 75 respondent. The dataof this research using primary data directly through a question nairean dan alyzedusing SPSS20. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. The result of thims study indicates that leadership stylebring a significanton toward performance based budgetingwith regression coefisient 0,321 and significant value 0,007 (alpha 0,05), this is shown by the result of tcount 2,762 which is higher than the ttable 1,995. the perfection of administrationbring a significanton toward performance based budgeting with regression coefisient 0,460 and significant value 0,006 (alpha 0,05), this is shown by the result of tcount 2,848 which is higher than the ttable 1,995, and human resourcebring a significanton toward performance based budgeting with regression coefisient 0,208 and significant value 0,028 (alpha 0,05), this is shown by the result of tcount 2,249 which is higher than the ttable 1,995. Whereas the reward does not effect the performance based budgetingwith regression coefisient 0,003 and significant value 0,991 (alpha 0,05), this is shown by the result of tcount 0,011 which is higher than the ttable 1,995. Punishment does not effect the performance based budgeting with regression coefisient 0,013 and significant value 0,956 (alpha 0,05), this is shown by the result of tcount 0,055 which is higher than the ttable 1,995.Keywords : leadership style, perfection of administration, human resources, reward,punishment